Additional Criminal Revocation of Access to Online Communication Devices for Perpetrators of Electronic-Based Sexual Violence - Maskun; Nur Azisa; Muhammad Mutawalli Mukhlis; M. Aris Munandar; Arnita Pratiwi Arifin (Universitas Negeri Semarang, 2025)
Advanced technology and information create many new problems that conflict with the values of decency and applied law in society. One phenomenon that is currently occurring is electronic-based sexual violence. It shows that there is a new type of crime that takes advantage of access to online communication in the mass media. This act clearly violates the provisions of the law regulating criminal acts of sexual violence. Even though basic criminal sanctions have been regulated, there are still shortcomings in the regulations. There is a need for additional criminal sanctions for perpetrators of electronic-based sexual violence, known as revocation of the right to access online communication devices. This research uses normative legal research methods with a statute approach and case approach. This research will comprehensively examine criminal law policies and the urgency of additional criminal sanctions for handling electronic-based sexual violence crimes. This research aims to provide new legal prescriptions regarding the regulation of sanctions for perpetrators of sexual violence who use and utilize internet-based communication devices.